Analiz makroekonomičeskih pokazatelej razvitiâ pribaltijskogo regiona posle vstupleiâ v ES i na sovremennom etap - Caurkubule, Zanna; Vishnevska, Alevtina (Analysis of the macroeconomic development of the Baltic region after the entry into the European Union at the present stage, 2010)
The article provides an analytical survey of development of the Baltic region (Lithuania, Latvia, Estonia) since joining the EU to present time in the context of the impact of the global economic and financial crisis on economic development of these countries. On the basis of comparative analysis of dynamics of change of the macroeconomic indicators of economic development in the Baltic States were made conclusions about absence of any prospect of the neoliberal model of development. This model has led Latvia to the actual loss of economic sovereignty and to the necessity to implement a new economic model focused on development of manufacture instead of redistribution of finances
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 143, s. 58-70
Keywords: Baltic region; economic development; financial crisis; neoliberal model of development